2021
DOI: 10.3389/fvets.2021.765495
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Analysis of Bovine Pasteurella multocida Serogroup A Strain Reveals Insights Into Virulence Attenuation

Abstract: Pasteurella multocida is one of the primary pathogens of bovine respiratory disease (BRD), and causes huge losses in the cattle industry. The Pm3 strain was a natural isolate, which is a strong form of pathogen and is sensitive to fluoroquinolones antibiotics. A high fluoroquinolone resistant strain, Pm64 (MIC = 64 μg/mL), was formed after continuous induction with subinhibitory concentration (1/2 MIC) of enrofloxacin, with the enhanced growth characteristics and large attenuation of pathogenicity in mice. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…One unanticipated finding was that the virulence of the satP gene deletion strain was several times lower than that of the wild-type strain, and we found that the treatment rate of the mice infected with ∆PmS was higher. This finding broadly supports the work of other studies in this area which links tolerance with virulence [47]. However, there are also some reports contrary to this study.…”
Section: Discussionsupporting
confidence: 92%
“…One unanticipated finding was that the virulence of the satP gene deletion strain was several times lower than that of the wild-type strain, and we found that the treatment rate of the mice infected with ∆PmS was higher. This finding broadly supports the work of other studies in this area which links tolerance with virulence [47]. However, there are also some reports contrary to this study.…”
Section: Discussionsupporting
confidence: 92%
“…First, Qubit was used for preliminary quantification, and the library was diluted to 1 ng/µL. Then, the Agilent 2100 BioAnalyzer was used to detect the insert size of the library [26]. The insert size was about 250-300 bp, in line with the expected Insert size.…”
Section: Transcriptomic Sequencingmentioning
confidence: 97%
“…CP00332), the tad locus contained the 14 intact genes that this locus typically harbors, i.e., flp1-flp2-tadV-rcpCAB-tadZABCDEFG (42). However, the specific involvement of tad genes in biofilm formation in P. multocida requires further evaluation as they are not conserved across all strains (38,39,(42)(43)(44)(45). The csrA gene is involved in glycogen synthesis and as a result, it plays a role in biofilm formation (7).…”
Section: Pasteurella Multocidamentioning
confidence: 99%
“…The csrA gene is involved in glycogen synthesis and as a result, it plays a role in biofilm formation (7). Other P. multocida genes with possible direct or indirect biofilm regulation roles include xylB, sgbU, hexD, aspA, comE, qseC, and pmorf0222 (7,43,(46)(47)(48). Of special interest is the qseC gene and its role in QS modulating the transcription of thousands of genes.…”
Section: Pasteurella Multocidamentioning
confidence: 99%